Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/(sici)1098-2388(199709/10)13:5<350::aid-ssu9>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Cystectomy and urinary diversion

Abstract: New insights into bladder cancer mechanisms have not yet produced clinical benefit. Without novel treatments, cystectomy remains the most effective local treatment, albeit the most aggressive. Uncertainty about the natural history of bladder cancer, the progression rate after other treatments, the risks of cystectomy and subsequent quality of life, foster debate about the indications for cystectomy. There are numerous urinary diversions and bladder substitutes. Differences in tumour extent, patient age, perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For patients diagnosed with muscle invasive bladder cancer (MIBC; approximately 30% of newly diagnosed BC patients) and those with high-risk progressive noninvasive disease, radical cystectomy with urinary diversion is the gold standard in treatment, providing excellent local cancer control 25 . Following cystectomy, urine can either be diverted into: a) an incontinent stoma (ileal conduit procedure); b) a continent urinary reservoir catheterized by the patient; or c) a continent urinary reservoir connected to the urethra (orthotopic neobladder) 6 . The physical and related psychological impact (e.g., urinary incontinence, sexual dysfunction, and poor body image) of these urinary diversion procedures on the patient’s quality of life (QOL) has been documented 27 .…”
Section: Introductionmentioning
confidence: 99%
“…For patients diagnosed with muscle invasive bladder cancer (MIBC; approximately 30% of newly diagnosed BC patients) and those with high-risk progressive noninvasive disease, radical cystectomy with urinary diversion is the gold standard in treatment, providing excellent local cancer control 25 . Following cystectomy, urine can either be diverted into: a) an incontinent stoma (ileal conduit procedure); b) a continent urinary reservoir catheterized by the patient; or c) a continent urinary reservoir connected to the urethra (orthotopic neobladder) 6 . The physical and related psychological impact (e.g., urinary incontinence, sexual dysfunction, and poor body image) of these urinary diversion procedures on the patient’s quality of life (QOL) has been documented 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract deterioration was found in 35% after 5-year followup and in 50% after 15-year followup. Skin irritations due to direct and continuous contact with urine, as well as constipation were also reported [7, 9]. …”
Section: Radical Cystectomymentioning
confidence: 99%
“…The emotional, functional, physical, and social impact of radical surgery on HRQOL significantly varies by the urinary diversion form [4, 7, 9, 12]. Studies have shown that ileal conduits are considered the easiest urinary diversion to perform surgically; however, [15] it is associated with significant psychological and practical side effects that can drastically reduce the emotional well-being of the patient [7, 9].…”
Section: Psychosocial Effects Of Urinary Diversionmentioning
confidence: 99%
“…The level of histone acetylation is determined by the concerted action between histone acetyltransferases (HATs) and histone deacetylases (HDACs) [101,102]. HATs catalyze the addition of an acetyl moiety from acetyl-CoA to the ε-amino groups of conserved positively charged lysine residues in the amino-terminal domains of the core histones [101][102][103]. This weakens their …”
Section: Histone Acetylation and Functional Specialization Of Chromatinmentioning
confidence: 99%
“…HDACs catalyze the opposite reaction and thereby reestablish the positive charge in the histones [101][102][103]. Alternatively, histone acetylation might provide an epigenetic marker for gene expression [104].…”
Section: Hdac4mentioning
confidence: 99%